Examining Social Dynamics by Using Slang Expressions in The Movie Scripts Entitled Barbie - Imelva Angely Silalahi; I Made Netra; Gede Primahadi Wijaya Rajeg (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The research titled “Examining Social Dynamics by Using Slang expressions in The Movie Scripts Entitled Barbie” adopts a qualitative approach to scrutinize the slang utilized by characters in the Barbie Movie, aiming to dissect the social dynamics depicted in the script. The study's main objective is to classify the diverse slang terms and comprehend their effect on the characters' social interactions and bonds. Employing Chapman’s (1988) classification of primary and secondary slang, the study organizes the slang found in the screenplay. It probes into how these terms influence character evolution, social ties, cultural variety, identity, and self-assertion. This examination underscores the role of slang in enriching thematic representation and advancing the movie's storyline. The results indicate that slang in "Barbie" serves beyond mere colloquialisms; it's a strategic narrative device that deepens character depiction and accentuates the intricate social interplay within the plot. The research deduces that slang is pivotal in crafting the movie's social milieu, offering profound insight into the personas and their interrelations, thereby enriching the audience's grasp of the cultural and societal contexts portrayed in the film.